1999
DOI: 10.1002/clc.4960220203
|View full text |Cite
|
Sign up to set email alerts
|

Early repolarization

Abstract: Summary:Early repolarization (ER) is an enigma. The purpose of this review is to reemphasize the overall electrocardiographic (ECG) pattern of this normal ST variant which continues to challenge the clinician because of its similarity to the current of injury potential to myocardium or an acute pericarditis. The data were provided from the studies identified through computerized searches of Medline, Toxline, Oxford, Agricola, and Bios Afterdark, Cumulative index, and a review of bibliographies of relevant arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 60 publications
2
77
2
2
Order By: Relevance
“…[5][6][7][8] However, because ERP (defined by the modified criteria of Haïssaguerre and colleagues 7 ) appeared intermittently, we based our calculation on both prevalent and incident cases and found that 23.9% manifested ERP at least once during follow-up, indicating that ERP was not a rare ECG finding. In past studies, only the prevalence, not incidence, of ERP has been reported because longitudinal studies covering the period before the diagnosis of ERP were lacking.…”
Section: Incidence Of Early Repolarization Patternmentioning
confidence: 98%
See 1 more Smart Citation
“…[5][6][7][8] However, because ERP (defined by the modified criteria of Haïssaguerre and colleagues 7 ) appeared intermittently, we based our calculation on both prevalent and incident cases and found that 23.9% manifested ERP at least once during follow-up, indicating that ERP was not a rare ECG finding. In past studies, only the prevalence, not incidence, of ERP has been reported because longitudinal studies covering the period before the diagnosis of ERP were lacking.…”
Section: Incidence Of Early Repolarization Patternmentioning
confidence: 98%
“…Using criteria similar to those of Haïssaguerre and colleagues, 7 we defined ERP cases as having (1) an elevation of the QRS-ST junction (J point) in notching formation (positive J deflection inscribed on the S wave) or of the ST segment in slurring formation (smooth transition from QRS complex to the ST segment) in at least 2 leads and (2) an amplitude of QRS-ST junction (J point) or ST-segment elevation Ն0.1 mV above the baseline as QRS notching or slurring in the inferior leads (II, III, aVF), lateral leads (I, aVL, V 4 through V 6 ), or both 7 ( Figure 1) at least once during follow-up. In slurring formation, because the transition from QRS complex to ST segment is smooth or the J point may be hidden in the QRS complex, we used Ն0.1 mV of the ST-segment elevation to indicate high-takeoff QRS-ST junction as the criterion.…”
Section: Definition and Confirmation Of Early Repolarization Pattern mentioning
confidence: 99%
“…The early repolarization syndrome (ERS) is a common electrocardiographic variant characterized by J-point elevation manifested either as QRS slurring (at the transition from the QRS segment to the ST segment) or notching (a positive defection inscribed on terminal S wave), STE with upper concavity and prominent T waves in at least 2 contiguous leads [7][8][9][10] . In most of the studies elevation of the J point and/or ST-segment from the baseline by at least 0.1 mV was considered definitive of ER 9,11 (figure 2).…”
Section: Early Repolarization Syndromementioning
confidence: 99%
“…7,8,17, 18 In most of the studies elevation of the J point and/or STsegment from the baseline by at least 0.1 mV was considered definitive of ER (Figure). 3,8…”
Section: Definition Of Early Repolarizationmentioning
confidence: 99%